Multi-scale Modeling Of Additive Manufacturing Process - Seet, Gim Lee (2016)
Additive manufacturing techniques, specifically those currently employed in metalbased manufacturing; involve heat transfer and fluid flow physics which are far too complex to be covered in an analytical form. This limits the control over material microstructure thus obtained in a deposited alloy component. To this need, a multi-scale numerical study is carried out combining a three-dimensional finite element (FE) based macro-scale and a cellular automaton (CA) based meso-scale model in order to simulate the dendritic grain growth in the selective laser melting (SLM) technique. The macro-scale model successfully simulates the heat transfer and fluid flow physics associated with a moving melt pool. The CA model deals with the phenomena of solute diffusion on a meso-scale during solidification. The thermal coupling between the two length scales results in a reasonably accurate model capable of accounting for steep thermal gradients, large cooling rates and complex thermal cycles associated with the solidification phenomena occurring during laser-based manufacturing process.